Maternal Distress during Pregnancy and Offspring Childhood Overweight - Katja Glejsted Ingstrup; Camilla Schou Andersen; Teresa Adeltoft Ajslev; Pernille Pedersen; Thorkild I. A. Sørensen; Ellen A. Nohr (Journal of Obesity)
Background. Maternal distress during pregnancy increases the intrauterine level of glucocorticoids, which may have long-term health consequences for the child. Objective. To examine if distress as a combined measure of anxiety, depression, and stress of the mother during pregnancy was associated with offspring childhood overweight at age 7. Methods. We performed a cohort study using prospective data from 37,764 women and child dyads from the Danish National Birth Cohort (1996–2002). At a telephone interview at approximately 30 weeks gestation, the women reported whether they felt anxious, depressed, or stressed. The 95 percentile for body mass index in an international reference defined childhood overweight at any given age. Logistic regression was used for the analyses. Results. The prevalence of overweight children at 7 years of age was 9.9%. Prenatal exposure to maternal distress during pregnancy was not associated with childhood overweight at 7 years of age (adjusted OR 1.06 (95% CI 0.96; 1.18)). In analyses stratified on sex, a small tendency of overweight was seen in boys (OR 1.15 (0.99; 1.33)), but not in girls (OR 0.98 (0.85; 1.13)). Conclusions. Maternal distress during pregnancy appeared to have limited, if any, influence on the risk of overweight in offspring at 7 years of age.